2013
DOI: 10.1111/1742-6723.12061
|View full text |Cite
|
Sign up to set email alerts
|

Blind prescribing: A study of junior doctors' prescribing preparedness in an Australian emergency department

Abstract: The majority of participants in the study had inadequate knowledge on medications they had most recently prescribed and medications most commonly prescribed in the ED. Junior doctors' perceptions of their medication knowledge were inflated in relation to their actual knowledge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 9 publications
1
15
0
Order By: Relevance
“…In some cases, doctors can either overestimate their knowledge (Starmer et al . ) or become overconfident with their abilities (Klein ). By contrast, complacency can be a product of overdependence on the clinical support system (Goddard et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In some cases, doctors can either overestimate their knowledge (Starmer et al . ) or become overconfident with their abilities (Klein ). By contrast, complacency can be a product of overdependence on the clinical support system (Goddard et al .…”
Section: Discussionmentioning
confidence: 99%
“…Further, the lack of adverse consequences makes clinicians believe that adverse events will not occur and gives them a false sense of security that their practice is satisfactory (Chassin & Loeb 2013). In some cases, doctors can either overestimate their knowledge (Starmer et al 2013) or become overconfident with their abilities (Klein 2005). By contrast, complacency can be a product of overdependence on the clinical support system (Goddard et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Theoretical framework Starmer and colleagues first described the phenomenon of 'blind prescribing' in a study of junior doctors' preparedness to prescribe medications in the ED (Starmer et al 2013, Eley et al 2014. They found significant knowledge deficits of commonly prescribed medications and revealed that the self-reported knowledge of junior doctors was greatly inflated compared with their measured level of knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…The concept of blind prescribing was used to describe the phenomenon among many of these prescribers' in their willingness to prescribe medications when medication knowledge was inadequate. Starmer et al (2013) hypothesized that this phenomenon could be negated by the increased use of reference materials, workplace assistance and education. Due to emergency nurses' ability to initiate/prescribe medications in a similar fashion, we hypothesize that the concept of 'blind prescribing' could exist.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation